Information literacy in research process among malaysian teacher trainees: expectation and inspiration of the ministry of education / Siri Sena Baba Hamid, Wan Ab Kadir Wan Dolah and Fuziah Mohd Nadzar. - Hamid, Siri Sena Baba; Wan Dolah, Wan Ab Kadir; Mohd Nadzar, Fuziah (Universiti Teknologi MARA Cawangan Selangor, 2015)
The research investigates Information Literacy (IL) competencies in ‘Seeking Skills’ involving accessing, evaluating and applying appropriate information that is coherent to the 21st century teacher trainees’ research requirements. The case study is designed as a qualitative exploratory, descriptive and explanatory survey that consist of a questionnaire survey on study population; and two face-to-face interviews with document analysis of theses from fourteen purposive samples taken from five northern states campuses. The study triangulates findings from questionnaire, in-depth interviews and document analysis to invoke trustworthiness by integrating quantitative and qualitative instruments to control bias. The findings signify a look back into the Malaysian Teacher Standards for realizing the Malaysian Education Blueprint 2015-2025. The study had found several factors lacking in the IL competencies that hindered the trainees’ research process in meeting expectations of the blueprint.